Sharia Property Business Development Strategy: IFAS and EFAS Matrix Model - Juliana Juliana; Hilda Monoarfa; Rika Jarianti (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2020)
The phenomenon of population growth is not in line with housing growth in Indonesia, which is the problem in this research. Besides, the current concept of homeownership still tends to use a conventional pattern based on ribawi, which is an obstacle for a Muslim to own a house. The purpose of this study is to determine the strategy of developing the Islamic property business from internal and external factors. The research method used is a quantitative method with data analysis techniques using the SWOT matrix analysis of IFAS (Internal Strategic Factors Analysis Summary) and EFAS (External Strategic Factors Analysis Summary). The population in this study were developers in the Greater Bandung area and the sampling used the convenience sampling method with a total sample of six expert respondents who were ready and willing to become respondents who represented academics, practitioners, and regulators. Based on the SWOT analysis with the IFAS and EFAS matrices, the results show that the position of the Islamic property business is in quadrant 1A, which is experiencing rapid growth. This quadrant shows that the right choice of strategy is rapid growth. The alternative strategy that is used as input is the S-O (Strength-Opportunities) business strategy so that the development strategy formulated is to use all strengths to seize and take advantage of the greatest possible opportunities. This research implies that the existence of business development efforts through SWOT analysis can strengthen the strategy to increase Islamic property and overcome the buying and selling of homeownership that is not yet following Islamic values.